A Blueprint to Address Research Gaps in the Development of Biomarkers for Pediatric Tuberculosis - Nicol, Mark Patrick (Clin Infect Dis, 2015)
Childhood tuberculosis contributes significantly to the global tuberculosis disease burden but remains challenging to diagnose due to inadequate methods of pathogen detection in paucibacillary pediatric samples and lack of a child-specific host biomarker to identify disease. Accurately diagnosing tuberculosis in children is required to improve case detection, surveillance, healthcare delivery, and effective advocacy. In May 2014, the National Institutes of Health convened a workshop including researchers in the field to delineate priorities to address this research gap. This blueprint describes the consensus from the workshop, identifies critical research steps to advance this field, and aims to catalyze efforts toward harmonization and collaboration in this area.